Technologies of Regenerative Endodontic Therapy – A Review - Ravindranath Megha, Alagarsamy Venkatesh2 , Dhakshinamoorthy Malarvizhi2 , Arunajatesan Subbiya3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Regenerative treatment is a recently advancing field in Endodontics. Newer treatment protocols andtechnologies are being put forward in this regard. This review is about some of the important aspects intechnologies of regenerative Endodontics.